Relationship between plasma and red blood cell concentrations of quinine in Brazilian children with uncomplicated Plasmodium falciparummalaria on oral therapy - Vieira, José L.F.; Gomes, Andreza L.S.; Borges, Larissa M.G.; Guimarães, Erika R. (Revista do Instituto de Medicina Tropical de São Paulo, 2009)
We determined the relationship between plasma and red blood cell concentrations of quinine in children with uncomplicated falciparum malaria from an endemic area of Amazonian region. Quinine was determined by high performance liquid chromatography with ultraviolet detection. In the steady state the ratio between plasma and red blood cell quinine concentration was 1.89 ± 1.25 ranging from 1.05 to 2.34. This result demonstrated that quinine do not concentrate in red blood cell of Brazilian children and characterize the absence of interracial difference in this relationship.